Controversies about the inheritance of sustainability models in the Brazilian beef chain - Bazanini, Roberto; Minuzzi Vilanova, Miguel Eugenio; Machado Júnior, Celso; Ryngelblum, Arnaldo Luiz (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This essay aims to propose a sustainability model applied to the Brazilian beef production chain. The proposed model seeks to integrate the sustainability indicators of the corporate models and the names of the literature, having as reference the incorporation of the Environmental, Social and Corporate Governance (ESG) principles to the cosmovision of the Stakeholder Capitalism Model. The literature review, based on previous models on sustainability, showed that these models have gaps that need to be filled so that the materiality matrix of Socio-Environmental Reports (CSR) is effectively contemplated so that one can go beyond the rhetorical resources disseminated as greenwashing in various sustainability publications. The objective of this essay resulted in the presentation to the academy of a specific methodological tool to be applied along the beef production chain that contemplates the ESG materiality matrix in line with the Declaration of the Davos Manifesto in 2020.